Sovereignty and the sea : how Indonesia became an archipelagic state - Butcher, John G.; Elson, R. E. (Robert Edward), 1947- (NUS Press, National University of Singapore, 2017)
"Until the mid-1950s nearly all of the sea between the far-flung islands of the Indonesian archipelago was open to ships of all nations, but in 1957, the Indonesian government declared that it had absolute sovereignty over all the waters lying within straight baselines drawn between the outermost islands of Indonesia. In this single step, Indonesia made its lands and seas a unified entity for the first time, a claim formally recognized in 1982 by the United Nations Convention on the Law of the Sea. Sovereignty and the Sea explores how Indonesia succeeded in its extraordinary claim despite its low international profile. John G. Butcher and R.E. Elson reveal that at the heart of Indonesia's archipelagic campaign was a small group of Indonesian diplomats whose dogged persistence, negotiating skills, and willingness to make difficult compromises resulted in Indonesia becoming the greatest archipelagic state in the world."